Identitas Politik Partai Keadilan Sejahtera - Titin Yuniartin Surahman (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2018)
This study discusses the political identity of Prosperous Justice Party (PKS). PKS is one of the parties based on Islam, but stands firmly in the auspices of the Unitary State of the Republic of Indonesia. PKS is born from harakah (movement), LDK-KAMMI-PK-PKS. The ideals of the Khilafah Islamiyah are always present in the ideals of the movement. Although in the auspices of plural and multicultural country, but the PKS still exists to adjust with the Republic of Indonesia. PKS political identity for some may seem gray. This is understandable, especially if we look at it from the perspective of incomplete Islamic understanding. The concept of caliphate of Islamiyah ala PKS is different from what is understood and developed in other harokah (movement). In essence, the Islamic caliphate that the PKS wants to uphold is international justice, international welfare, international harmony, and world prosperity. It starts from building prosperity, harmony, and national justice.